Chemistry of surface water, precipitation, throughfall, leaves, sediment, soil, and air near a gold mining region in Peru. Issue 5 (17th March 2022) - Gerson, Jacqueline R.; Szponar, Natalie; Agostini, Arianna; Alotaibi, Rand; Bergquist, Bridget; Chen, Arabella; Fernandez, Luis E.; Lansdale, Kelsey N.; Lee, Anne H.; Machicao, Maria F.; Marchese, Melissa J.; Topp, Simon N.; et al.
Abstract: Artisanal and small‐scale gold mining (ASGM) is the primary global source of anthropogenic mercury (Hg) emissions and a large source of landscape change. ASGM occurs throughout the world, including in the Peruvian Amazon. This data set contains measurements of surface water, precipitation, throughfall, leaves, sediment, soil, and air samples from across the Madre de Dios region of Peru, in locations near and remote from ASGM. These data were collected to determine the fate and transport of Hg across the landscape. Samples were collected in 2018 and 2019. Data predominantly included total Hg and methyl Hg concentrations in surface water, precipitation, throughfall, leaves, sediment, soil, and air. Additional water and soil parameters were also measured to better characterize their chemistry. There are no copyright restrictions; please cite this data paper when the data are used in publication.